Investigation of modal strain energy for varying ribs orientation concept of untapered wing box model - Nee, Chan Ying; Mohd Rafie, Azmin Shakrine; Harmin, Mohammad Yazdi (The Aeronautical and Astronautical Society of the Republic of China, 2022)
The variable ribs' orientation concept is becoming one of the promising options for innovative wing box design for aircraft whereby several previous studies have shown that significant improvement in aeroelastic characteristics can be acquired without any increment in weight. This paper presents further investigation that has been conducted with respect to strain energy of flutter modes. Two different untapered wing-box configurations of the unswept and sweptback planforms are considered and the comparison is made between the best-found solution against the reference baseline configuration. Based on the findings, the strain energy is found at a greater magnitude for the variable ribs that are located between the middle section and the root section of the wing. This demonstrates significant stiffness improvement that is contributed by the ribs at this location.